Statistical convergence on non-Newtonian calculus - Yilmazer, Mehmet Cagri; Yilmaz, Emrah; Goktas, Sertac; Et, Mikail (Springernature, 2023)
Our aim is to give concepts of density, statistical convergence, statistically Cauchy sequence, Ces & agrave;ro summability and k -statistical convergence on non-Newtonian calculus. Especially, if a generator on this calculus is determined as identity function, all results in the classical case are reached.
Keywords: Statistical convergence; Statistical Cauchy sequence; Cesaro convergence; Non-Newtonian calculus